2023
DOI: 10.1021/acs.jchemed.3c00500
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Performance of College Chemistry Students with ChatGPT for Calculations Involving Acids and Bases

Ted M. Clark,
Ellie Anderson,
Nicole M. Dickson-Karn
et al.

Abstract: Student performance on open-response calculations involving acid and base solutions before and after instruction in general chemistry and analytical chemistry courses was compared with the output from the artificial intelligence chatbot ChatGPT. Applying a theoretical model of expertise for problem solving that includes problem conceptualization, problem strategy, and solution, it is found that students errors following instruction primarily involved problem conceptualization and the misapplication of heuristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
2
22
1
Order By: Relevance
“…Investigations have considered ChatGPT performance on exam questions from courses such as general chemistry and pharmaceutical science . More specific content investigations with a focus on acid/base calculations and organic chemistry have also been reported. Notably critical evaluations of ChatGPT performance on chemistry tasks have also resulted in these broad efforts to probe content accuracy. , …”
Section: Introductionmentioning
confidence: 99%
“…Investigations have considered ChatGPT performance on exam questions from courses such as general chemistry and pharmaceutical science . More specific content investigations with a focus on acid/base calculations and organic chemistry have also been reported. Notably critical evaluations of ChatGPT performance on chemistry tasks have also resulted in these broad efforts to probe content accuracy. , …”
Section: Introductionmentioning
confidence: 99%
“…A complete computational notebook containing all necessary code and results is provided online. 3 In principle, similar results could be obtained following Clark et al's process of typing the entries into the web browserbased ChatGPT Plus; 4 programming merely avoids tedious data entry.…”
mentioning
confidence: 65%
“…The problems and errors of LLM outputs discussed by Clark et al are only true for their specific choice of GPT-3.5; these limitations are mostly resolved by using a better model and entirely resolved by using an improved prompt and calculator tool. Teachers should assume that students already have access to this functionality; eventually, it will be the default.…”
Section: Implications For Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark also asked ChatGPT-3.5 to solve a set of 15 multiple-choice general chemistry cumulative final exam questions and found that the chatbot was able to answer 40% of the questions correctly contrasting with the 76% student average . Clark and colleagues conducted a follow-up study specifically on questions involving acid and base calculations . Generally, ChatGPT-3.5 could calculate pH involving strong acids/bases and volume for neutralization well but performed weaker for problems involving weak acids/bases and aqueous salts and could not calculate pH for titration questions.…”
Section: Introductionmentioning
confidence: 99%